Abuse of authority as a ground for liability of bodies and persons performing the functions of business entities - V. H. Zhornokui (Law and Safety)
The current state of legal doctrine and court practice on the issues of authority abuse as a ground for liability of bodies and persons performing the functions of business entities has been analysed. Since a business entity forms its own will and implements it through its bodies and persons performing the functions of its agencies, the relevant persons must adhere to the powers defined by law and the charter. If they act beyond their own powers, the will of such a legal entity is distorted and their own will, the will of individuals, takes place.